PERLINDUNGAN HUKUM BAGI PEMEGANG SAHAM MINORITAS YANG TIDAK DILIBATKAN DALAM PROSES AKUISISI - Maya Sari; Abdul Rahcmad Budiono; Hanif Nur Widhiyanti (Universitas Airlangga, 2017)
Acquisition as a form of corporate restructuring that is carry out to overcome the situation of financial difficulties or improve the performance of the company as a whole or part of the business unit. In Article 126 paragraph 1 of Laws of the Republic of Indonesia number 40 of 2007 concerning Limited Liability Company stated that the acquisition process should consider the interests of minority shareholders. However, sometimes acquisition decisions have already been decided in advance by the majority shareholder without involving minority shareholders. Based on this, this paper intends to analyze the form of legal protection for minority shareholders who are not involved in the acquisition process. Through the approach of legislation and case approach, it is found that Laws of the Republic of Indonesia number 40 of 2007 concerning Limited Liability Company has not provided enough legal protection to minority shareholders. The decision-making process of acquisition in the General Meeting of Shareholders should be procedurally and substantively in accordance with Laws of the Republic of Indonesia number 40 of 2007 concerning Limited Liability Company. It is intended that minority shareholders have the opportunity to exercise their voting rights even though they do not have to be the party controlling the company.